2021
DOI: 10.1007/s00345-021-03793-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of age with response to preoperative chemotherapy in patients with muscle-invasive bladder cancer

Abstract: Purpose To assess the association of patient age with response to preoperative chemotherapy in patients with muscle-invasive bladder cancer (MIBC). Materials and methods We analyzed data from 1105 patients with MIBC. Patients age was evaluated as continuous variable and stratified in quartiles. Pathologic objective response (pOR; ypT0-Ta-Tis-T1N0) and pathologic complete response (pCR; ypT0N0), as well survival outcomes were assessed. We used data of 395 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…We were able to confirm a recent study that the response to inductive chemotherapy in bladder cancer is independent from age [ 23 ]. Discrepant from another trial, we found no association between the number of removed lymph nodes and cancer-specific survival [ 24 ].…”
Section: Discussionsupporting
confidence: 84%
“…We were able to confirm a recent study that the response to inductive chemotherapy in bladder cancer is independent from age [ 23 ]. Discrepant from another trial, we found no association between the number of removed lymph nodes and cancer-specific survival [ 24 ].…”
Section: Discussionsupporting
confidence: 84%
“…All patients were chemotherapy-naïve. We investigated a panel of genes on the basis of prior reports, current ongoing prospective trials, and genes found to have the highest mutation rates in the MSK/The Cancer Genome Atlas (TCGA) cohort [2] , [9] , [12] , [13] , [14] . All data used for this analysis are available at https://cbioportal.org .…”
Section: Methodsmentioning
confidence: 99%
“…Neoadjuvant chemotherapy (NAC) with a cisplatin-based combination followed by radical cystectomy (RC) is the standard of care for patients with cT2–4N0M0 muscle-invasive bladder cancer (MIBC) who are cisplatin-eligible [1] . Although current evidence supports an overall improvement in survival, not every patient will benefit from NAC [2] , [3] . Patient selection is of paramount importance in order to identify those who will not respond to NAC to avoid NAC toxicity and a delay to definitive therapy.…”
Section: Introductionmentioning
confidence: 94%